2017
DOI: 10.1371/journal.pone.0172433
|View full text |Cite
|
Sign up to set email alerts
|

Non-small cell lung cancer: Whole-lesion histogram analysis of the apparent diffusion coefficient for assessment of tumor grade, lymphovascular invasion and pleural invasion

Abstract: PurposeInvestigating the diagnostic accuracy of histogram analyses of apparent diffusion coefficient (ADC) values for determining non-small cell lung cancer (NSCLC) tumor grades, lymphovascular invasion, and pleural invasion.Materials and methodsWe studied 60 surgically diagnosed NSCLC patients. Diffusion-weighted imaging (DWI) was performed in the axial plane using a navigator-triggered single-shot, echo-planar imaging sequence with prospective acquisition correction. The ADC maps were generated, and we place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Another study showed that skewness and kurtosis of histogram analysis from ADC map were able to differentiate thyroid carcinoma with lymph node metastasis from that without metastasis (32). In the study of non-small cell lung cancer, higher ADC skewness and kurtosis were associated with lymphovascular invasion and pleural invasion (34). In a study of pediatric diffuse intrinsic potine glioma using 18 F-FDG PET and MRI ADC histogram, higher ADC skewness and kurtosis of the enhancing portion of the tumor were associated with shorter PFS (16).…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that skewness and kurtosis of histogram analysis from ADC map were able to differentiate thyroid carcinoma with lymph node metastasis from that without metastasis (32). In the study of non-small cell lung cancer, higher ADC skewness and kurtosis were associated with lymphovascular invasion and pleural invasion (34). In a study of pediatric diffuse intrinsic potine glioma using 18 F-FDG PET and MRI ADC histogram, higher ADC skewness and kurtosis of the enhancing portion of the tumor were associated with shorter PFS (16).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic free-breathing steady-state free precession MRI has been used to assess the movement of a tumor abutting the chest wall during breathing with 88.5% accuracy [ 18 ]. The whole-lesion histogram analysis of the apparent diffusion coefficient could assist in the assessment of pleural invasion [ 19 ]. However, to the best of our knowledge, no previous studies have distinguished PL1 from PL2 pleural invasion.…”
Section: Discussionmentioning
confidence: 99%
“…27 In their study investigating NSCLC type lung cancers, Tsuchiya et al found an association between skewness, kurtosis and pleural, lymphovascular invasion, while no association was reported between these histogram parameters and tumor grade which might support our results. 28…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we lacked the information that might alter the ADC histogram results such as genetic mutations in lung cancer histological types and NSCLC histological grade information. 25,28 Fifth, DWI data obtained with only 1.5-T MRI system was included in the study. Future studies utilizing different magnetic fields are warranted to confirm our findings and compare the results of different scanners.…”
Section: Discussionmentioning
confidence: 99%